Description of ‘Blautia phocaeensis’ sp. nov. and ‘Lachnoclostridium edouardi’ sp. nov., isolated from healthy fresh stools of Saudi Arabia Bedouins by culturomics - S.I. Traore; E.I. Azhar; M. Yasir; F. Bibi; P.-E. Fournier; A.A. Jiman-Fatani; J. Delerce; F. Cadoret; J.-C. Lagier; D. Raoult (New Microbes and New Infections, 2017)
We report here the main characteristics of ‘Blautia phocaeensis’ strain Marseille-P3441 sp. nov. and ‘Lachnoclostridium edouardi’ strain Marseille-P3397 sp. nov., that were isolated from a faecal specimen of a 42-year-old female Saudi Bedouin. We used a bacterial culturomics approach combined with taxono-genomics.